The House of Desserts / Awang Aznil Awang Zainudin ... [et al.] - Awang Zainudin, Awang Aznil; Rosli, Siti Nur Anisah; Kawi, Siti Farahanah; Johari, Zaharah (2014)
Our company "The House of Desserts" is a type of cafe that sells many kinds of desserts. Our company deals with the food industry, whereby we consider the quality and the tastiness of our desserts. Eventhough this type of cafe already existed, we are sure that our cafe will give us tremendous profit and opportunity because of our unique and tasty desserts. The name of our cafe was suggested by one of our partner, and is agreeable by others. It is simple yet it describes what our cafe is about. Our cafe will be focusing on a high quality of services, high quality of desserts, creative promotions and continues development of employees. We expected it to be successful in less than one year. We also have a strategic location for our cafe, which is located in Perdana Park, Tanjung Aru. As we all know, Perdana Park is a recreational park that is famous for its beautiful environment and colourful water fountain. It always attracts people from inside and outside of the country. Our chosen target market includes 40% of teenagers and children, 20% from the nearby residents and 40% of young and married couple. We are sure to attract young and married couple as we offer catering for special occasions such as birthday party. We will give the customers full support in preparing for the occasions, whereby the customer will not need to prepare their own table for the desserts. Our competitor would be Cupcake Chic, Multibake and Southern which located in Centre point. Our business and the competitors business focus on the same target market and pricing structures as ours. What will make our cafe is much special is that we offer catering services, Wi-Fi and special pricing for our members. With consistent care of the quality of our service and product, we are sure to get more than 50% of loyal customers. In the future, we have planned to expand our business to other district that has the potential in succeeding our business. We also want to expand our business to Sarawak and peninsular Malaysia. We want our cafe well known in all parts of Malaysia. The possibility of it to come true is very high as nowadays, people love to eat desserts. We will have variety designs, flavor, decorations and unique packaging. This way, we can retain our customers' loyalty. We will also focus on building strategic relationships with our suppliers, customers, friends and family. Building relationship with the suppliers will give us many benefits, such as we can gain more discount on raw materials. Relationship building with the customers will increase the loyalty of our customers. Meanwhile, building much more strategic relationship with our friends and family will give us benefits in terms of advertising. When the relationship is strategic, surely they will help us to promote our cafe to other people. Thus, it can make our cafe well known to the peoples. The contribution that our cafe can give to the society and country is by providing them job opportunities and the development of the country's economy sector. The capital that we use for this cafe will be financed from the partner, which is amounted up to RM 80, 000, and loan from the bank. By that.we are sure to run our business effectively and efficiently. We also believed that through the efforts contributed by the partners in this business, we would achieve our goals, objective, vision and mission.